Can service members with mild traumatic brain injury learn to develop implementation intentions for self-identified goals?. Issue 12 (5th June 2022) - Radomski, Mary Vining; Giles, Gordon Muir; Owens, Jenny; Showers, Mark; Rabusch, Stacey; Kreiger, Rob; Zola, Joette; Kath, Kristina
Abstract: Purpose: Goal achievement relies heavily on executive functions, which may be compromised following mild traumatic brain injury (mTBI). Implementation intentions (II) have been found to help people act in accordance with their goals. II are written statements that describe a behavior that a person plans to enact when they encounter some form of anticipated trigger or stimulus. We evaluated the feasibility of teaching participants with mTBI to develop II for self-identified goals within the context of cognitive rehabilitation. Methods: Soldiers with mTBI were recruited from a traumatic brain injury clinic. During the intervention, participants were assigned to develop an II for one of three self-identified goals every day. Descriptive methods were used to examine implementability and acceptability of the II training protocol as well as the extent to which participants learned to develop II for their own goals. Results: The II training protocol was found to be highly implementable and acceptable to participants. Overall, participants ( n = 16) were able to develop II related to their self-identified goals, which primarily focused on managing cognitive problems. For the most part, participants developed II that involved event- rather than time- or somatic/feeling-based triggers. Conclusion and implications: Participants with mTBI were able to learn to develop II for their self-identified goals. Further study is needed to determine whether adding II to cognitive rehabilitation advances patient goal achievement. IMPLICATIONS FOR REHABILITATION: It is feasible to incorporate training in implementation intentions (predetermined "if/when-then" plans that are intended to link specific situational triggers with actions) in metacognitive strategy instruction for patients with mild traumatic brain injury. Participants with mild traumatic brain injury in this study demonstrated that they were able to develop implementation intentions for multiple self-identified rehabilitation goals, which holds promise for also teaching patients with mild cognitive impairment from other conditions. Learning to develop implementation intentions may help patients with mild traumatic brain injury initiate a range of other cognitive strategies in their everyday lives. Implementation intentions have the potential to help patients enact goal behaviors associated with their rehabilitation goals, making cognitive rehabilitation more "customizable" and relevant to clients' specific needs.